2023
DOI: 10.3390/agronomy13061450
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Transcriptome and Metabolome Analysis Reveal That Exogenous Gibberellin Application Regulates Lignin Synthesis in Ramie

Abstract: Gibberellin regulates plant growth, development, and metabolic processes. However, the underlying mechanism of the substantial effect of gibberellin on stem height and secondary metabolites in forage ramie is unclear. Therefore, this study combined transcriptomic and metabolomics analyses to identify the mechanisms regulating growth and secondary metabolite contents in forage ramie following exogenous gibberellin application. Exogenous gibberellin application significantly reduced the lignin content in the lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Meanwhile, the cluster and class heatmaps showed the similarity of components among biological repeats and the difference of components among the two treatment groups, suggesting that GA3 strongly influenced the metabolite profiles in the stem bark of P. chinense Schneid seedlings (Figure S4b). In this present study, a total of 443 metabolites in stem bark samples from CK and GA3 treatment groups were identified and divided into 11 categories, which mainly included flavonoid (90), phenolic acid (62), lipid (59), amino acid and derivative (46), alkaloid (45), organic acid (31), nucleotide and derivative (30), and lignan and coumarin (20) (Figure S4c).…”
Section: Differentially Accumulated Metabolites (Dams) Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the cluster and class heatmaps showed the similarity of components among biological repeats and the difference of components among the two treatment groups, suggesting that GA3 strongly influenced the metabolite profiles in the stem bark of P. chinense Schneid seedlings (Figure S4b). In this present study, a total of 443 metabolites in stem bark samples from CK and GA3 treatment groups were identified and divided into 11 categories, which mainly included flavonoid (90), phenolic acid (62), lipid (59), amino acid and derivative (46), alkaloid (45), organic acid (31), nucleotide and derivative (30), and lignan and coumarin (20) (Figure S4c).…”
Section: Differentially Accumulated Metabolites (Dams) Analysismentioning
confidence: 99%
“…Secondary metabolites comprise a diverse group of compounds, including flavonoids, alkaloids, and terpenoids, where flavonoids play a protective role against biotic and abiotic stresses. The biosynthesis of these compounds is regulated by exogenous GA 3 in plants [19,20]. Previous studies have validated that exogenous GA 3 inhibited the biosynthesis of flavonoid and isoflavonoid through negatively regulating GA-mediated signal pathway and promoted the growth by improving nitrogen metabolism in Medicago truncatula [21].…”
Section: Introductionmentioning
confidence: 99%
“…The priming of barley seed with GB3 reduces the toxic effects of Cd stress on coleoptile growth [85]. Gibberellin improves ramie growth, development, and metabolic processes [86,87]. The study indicated that brassinosteroids (BR) and gibberellin (GA) have different effects on the enrichment and transport of Cd in ramie.…”
Section: Agronomic Approaches To Enhance CD Tolerance In Ramiementioning
confidence: 99%
“…Furthermore, GA regulates growth by controlling the size of the meristem, thereby controlling the cell production rate (Kiradjiev and Band 2023). Even the integrated analysis of transcriptome and metabolome reveals that exogenous GA has a substantial effect on stem height and secondary metabolites in forage ramie (Jie et al 2023). Jang et al (2023) illustrated that the ABA and GA balance is not an absolute factor in determining dormancy.…”
Section: Introductionmentioning
confidence: 99%